Medios masivos de comunicación y su impacto en la identidad cultural de los habitantes del Sector El Guayabo, Parroquia Moraspungo, Cantòn Pangua, año 2019 - Manotoa Manotoa, Johana Alejandra (2019)
In this final research report prior to obtaining a bachelor's degree in social communication, it has as its theme mass media and its impact on the cultural identity of the inhabitants of the El Guayabo sector, Moraspungo Parish, Canton Pangua, year 2019, whose main The purpose is to determine how these media are impacting the traditions and customs of the sector. The mass media currently perform various functions within a society such as: educate, entertain, inform, persuade etc, one of the great advantages of these channels is the immediacy with which information is presented, regardless of time and space in which such an event took place. Today the media have evolved in a transcendental way, which has had repercussions in several areas, especially the socio-cultural environment of a region, country, town or community. The MMCs, due to the massive information they present in their contents, are damaging the cultural identity of the sector studied because many people, especially young people, are guided by what they read, see or simply listen to, which in an indirect way they are inculcating to impose diverse styles, dialects, idioms and cultural scenarios outside the place. It also establishes the development of a training plan to help strengthen and keep alive the traditions, customs and cultural values of the town.